Identification of Cytosolic DNA Sensor cGAS-STING as Immune-Related Risk Factor in Renal Carcinoma following Pan-Cancer Analysis - Zheng Wu; Ying Lin; Li-Min Liu; Yan-Li Hou; Wei-Ting Qin; Lei Zhang; Shu-Heng Jiang; Qin Yang; Yong-Rui Bai (Journal of Immunology Research)
Background. The cytosolic DNA sensor cyclic GMP-AMP synthase (cGAS) plays critical functions in innate immune responses via the production of the second messenger cyclic guanosine monophosphate-adenosine monophosphate (cGAMP), which stimulates the adaptor stimulator of interferon genes (STING). However, the clinical relevance and prognostic value of the cGAS-STING pathway in human cancers remains largely unexplored. Methods. A gene signature related to the cGAS-STING score was identified. The pan-cancer landscape of cGAS-STING expression was calculated using the RNAseq data acquired from the TCGA cohort. Tumor-infiltrating immune cells (TIICs) were determined by the ssGSEA method. Kaplan–Meier curves, Cox regression analyses, and the area under the curve (AUC) were employed to decipher the predictive value of cGAS-STING risk score and TIICs across several human cancers. Results. Most tumor tissues displayed a higher cGAS-STING score compared with their corresponding nontumor tissues, except for prostate adenocarcinoma (PRAD) and uterine corpus endometrial carcinoma (UCEC). Higher cGAS-STING score was closely associated with poor clinical outcome of kidney renal clear cell carcinoma (KIRC) and kidney renal papillary cell carcinoma (KIRP), whereas the cGAS-STING score predicted a better prognosis in pheochromocytoma and paraganglioma (PCPG). Enrichment analysis showed that cGAS-STING was profoundly implicated in diverse immune-related pathways in KIRC, KIRP, and PCPG. Significant positive correlations were noticed between cGAS-STING score and TIICs, including activated CD8+ T cells, activated CD4+ T cells, monocytes, and mast cells. Finally, the cGAS-STING score was revealed to be an independent prognostic factor for KIRC patients and possessed a strong predictive power for the prognostic evaluation of KIRC and KIRP patients. Conclusions. We constructed a cGAS-STING gene signature to predict survival and tumor immunity across human cancers, which can serve as a novel prognostic indicator and therapeutic target, especially in KIRC and KIRP.